Fundamentals Of Economics - EN26 - 202301 - Castro Herrera, Soraya Beatriz (2023)
Fundamentals of Economics focuses on providing students with theoretical and practical elements regarding four (5) main themes: Market Process, Consumer Theory, Theory of the Firm, Perfect Competitive Markets and Monopoly, and Economic Welfare. Purpose: The course develops abstraction abilities and economic intuition by means of applying basic mathematical and graphical tools. It focuses in the Level 1 development of the General Competence of Quantitative Reasoning.